The "Nekuia's" End (Od. 568-640) - González Merino, Juan Ignacio (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2013)
The Nekuia’s end, despite it fi ts perfectly into the structure of Od. 11, presents a few peculiarities, the most important of which is a vision of the kingdom of Hades full of life, against the dominant belief in the Homeric poems in the inanity of life of souls in the afterlife. In the detailed analysis of the differents episodes of the Nekuia´s end, some comic features are detected , even grotesque. The protagonists of these episodes also are shown burdened (Minos, Orion), when not victims of terrible punishments (the three sinners). All this serves to indirectly discredit the belief in a happy life in the Hereafter resembling the earthly life. As a culmination the pretended Odysseus´s catabasis is discussed, that is not one, which reaffi rmed, against the mysteric doctrine, that no one can go down to Hades kingdom and return to the world of the living.